Transgenic mouse model harboring the transcriptional fusion Ccl20-luciferase as a novel reporter of pro-inflammatory response - Crispo, M. (2013)
The chemokine CCL20, the unique ligand of CCR6 functions as an attractant of immune cells. Expression of CCL20 is induced by Toll-like Receptor (TLR) signaling or proinflammatory cytokine stimulation. However CCL20 is also constitutively produced at specific epithelial sites of mucosa. This expression profile is achieved by transcriptional regulation. In the present work we characterized regulatory features of mouse Ccl20 gene. Transcriptional fusions between the mouse Ccl20 promoter and the firefly luciferase (luc) encoding gene were constructed and assessed in in vitro and in vivo assays. We found that liver CCL20 expression and luciferase activity were upregulated by systemic administration of the TLR5 agonist flagellin. Using shRNA and dominant negative form specific for mouse TLR5, we showed that this expression was controlled by TLR5. To address in situ the regulation of gene activity, a transgenic mouse line harboring a functional Ccl20-luc fusion was generated. The luciferase expression was highly concordant with Ccl20 expression in different tissues. Our data indicate that the transgenic mouse model can be used to monitor activation of innate response in vivo.